The Productivity Commission and industrial relations reform. (June 2016) - Peetz, David
This article considers the political economy of the Productivity Commission in industrial relations reform; in particular, its review of the industrial relations framework foreshadowed in 2013 and conducted in 2015. Following a history of the establishment of the Productivity Commission and its predecessor agencies, it argues that the concepts of third-party independence and third-party endorsement are important for understanding the role of the Productivity Commission. A review of the politics of industrial relations reform leads into the central analysis of the political economy of the Productivity Commission's 2015 inquiry into the Australian workplace relations framework. The concepts of third-party independence and endorsement are applied in analysing some of the inquiry's key recommendations. The conclusion discusses several difficulties in the political economy of the Productivity Commission and its relationships to government and, indeed, to evidence, when the latter contradicted its mainly liberal market stance.